Perempuan dan Politik: Studi Komunikasi Politik tentang Keterwakilan Perempuan di Legislatif - Mukarom, Zaenal (Mediator, 2008)
In order to encourage women’s active role to participate in political world, especially to meet the demand of Electoral Regulation, a portion of 30% electoral committee was dedicatedas minimum allocation for women. To meet those demands, a political communication strategy was needed. The strategy could be implemented by women themselves, or political party. Women political communication strategy was carried out by applying a counter of political communication: gender mainstreaming, affirmative action, political education for women, and civic education for women. Meanwhile, political parties conducted their political communication by utilizing media and message strategy. Message strategy was implemented by employing political marketing mix consisted of product, promotion, price, and place. Media strategy appeared by diffusion of innovation approach by emphasizing gendermainstreaming issues among public.